1.85. Napisz wzór funkcji, której wykres otrzymamy w wyniku przekształce wykresu funkcji f(x) = (3 – x)/(2x) przez symetrię względem: a) osi OX b) osi OY. c) f(x) = – (x ^ 3 + 1) f) f(x) = (- x + 2) ^ 2 4 3 2 2 1 0 3 4 y y = f(x) -6-5-4-3-2-1 1 2 3 4 5 6 X

1.85. Napisz wzór funkcji, której wykres otrzymamy w wyniku przekształce wykresu funkcji f(x) = (3 – x)/(2x) przez symetrię względem: a) osi OX b) osi OY. c) f(x) = – (x ^ 3 + 1) f) f(x) = (- x + 2) ^ 2 4 3 2 2 1 0 3 4 y y = f(x) -6-5-4-3-2-1 1 2 3 4 5 6 X